Developing an in-Line method to improve mechanical and flame retardancy performance of polyethylene fiber. (10th July 2022) - Gunaydin, Beyzanur; Seyhan, Aybeniz; Polat, Yusuf; Kilic, Ali; Demir, Ali; Ureyen, Mustafa Erdem; Avci, Huseyin
Polyethylene (PE) has high flammability and can be quickly burned under atmospheric conditions without leaving any residues. This study presents PE fibers produced by a novel modified melt spinning line to enhance mechanical and flame retardancy properties. Scanning electron microscopy equipped with energy dispersive X-ray, thermogravimetric analysis, limiting oxygen index, micro combustion calorimeter and tensile tests were performed to reveal morphological, thermal and mechanical characteristics of the fibers. An organic phosphorus additive was used to provide flame retardancy in addition to mechanical performance in one-step production. Subsequently, the produced fibers were subjected to the hot drawing, increasing modulus values from 135 MPa to 2.8 GPa. In addition, phosphorus-treated fibers exhibited a limiting oxygen index (LOI) value of 21.5, leaving some residue at 600°C. Furthermore, a decrease in the peak heat release rate (pHRR) was observed in all samples compared to the control sample for the micro combustion calorimeter (MCC) test. Looking at the decrease in heat release (HR), the best result belongs to zone II with 50 and 95°C produced at 1000 m/min take-up speed for the samples. Moreover, about 23%, 23%, and 18% decreases were observed in HR capacity, pHRR, and total HR values, respectively. The modified spinning system is capable of continuous production of flame retardant linear low-density polyethylene (LLDPE) fibers, which can find widespread applications in aviation, automotive, and defense industries.